A review of technologies for direct lithium extraction from low Li+ concentration aqueous solutions - Murphy, Olivia; Haji, Maha N. (Frontiers in Chemical Engineering, 2022)
Under the Paris Agreement, established by the United Nations Framework Convention on Climate Change, many countries have agreed to transition their energy sources and technologies to reduce greenhouse gas emissions to levels concordant with the 1.5°C warming goal. Lithium (Li) is critical to this transition due to its use in nuclear fusion as well as in rechargeable lithium-ion batteries used for energy storage for electric vehicles and renewable energy harvesting systems. As a result, the global demand for Li is expected to reach 5.11 Mt by 2050. At this consumption rate, the Li reserves on land are expected to be depleted by 2080. In addition to spodumene and lepidolite ores, Li is present in seawater, and salt-lake brines as dissolved Li+ ions. Li recovery from aqueous solutions such as these are a potential solution to limited terrestrial reserves. The present work reviews the advantages and challenges of a variety of technologies for Li recovery from aqueous solutions, including precipitants, solvent extractants, Li-ion sieves, Li-ion-imprinted membranes, battery-based electrochemical systems, and electro-membrane-based electrochemical systems. The techno-economic feasibility and key performance parameters of each technology, such as the Li+ capacity, selectivity, separation efficiency, recovery, regeneration, cyclical stability, thermal stability, environmental durability, product quality, extraction time, and energy consumption are highlighted when available. Excluding precipitation and solvent extraction, these technologies demonstrate a high potential for sustainable Li+ extraction from low Li+ concentration aqueous solutions or seawater. However, further research and development will be required to scale these technologies from benchtop experiments to industrial applications. The development of optimized materials and synthesis methods that improve the Li+ selectivity, separation efficiency, chemical stability, lifetime, and Li+ recovery should be prioritized. Additionally, techno-economic and life cycle analyses are needed for a more critical evaluation of these extraction technologies for large-scale Li production. Such assessments will further elucidate the climate impact, energy demand, capital costs, operational costs, productivity, potential return on investment, and other key feasibility factors. It is anticipated that this review will provide a solid foundation for future research commercialization efforts to sustainably meet the growing demand for Li as the world transitions to clean energy.